MODEL PERENCANAAN KURIKULUM BERBASIS PESANTREN UNTUK MEMPERKAYA PENDIDIKAN FORMAL DI MA AL-INAYAH - Rizkarima; Nur Fathiyya Zahira Mujahidah (Epistemic: Jurnal Ilmiah Pendidikan, 2026)
This study analyses the implementation of a pesantren-based curriculum in non-boarding madrasahs, which still face challenges in fostering religious character due to the lack of a boarding system. The study aims to formulate an adaptive curriculum implementation model for this context through a qualitative approach using a case study design at Madrasah Aliyah Al-Inayah in Bandung. Data were collected from students and teachers via questionnaires (n?54 respondents), in-depth interviews with the deputy head of the madrasah responsible for the curriculum, and limited observation, and were subsequently analysed using a thematic approach. The research findings indicate that curriculum implementation occurs through four main components: the integration of values into the learning process, the cultivation of religious practices, the exemplary behaviour demonstrated by teachers, and cooperation between the school and the family. These four components were identified as a single system forming a model for the implementation of an integrative-collaborative pesantren curriculum, with the ‘One Day One Student’ programme serving as a mechanism for reinforcement outside the school environment. This study produced a contextual, values-based curriculum implementation model for non-boarding madrasahs.